THE EFFECT OF SERVICE RECOVERY JUSTICE PERCEIVED SATISFACTION AND IMPACT ON RELATIONSHIP QUALITY, AND PURCHASE INTENTION AT PT INDOTRUCK UTAMA AS ONE OF VOLVO TRUCKS INDONESIA’S DEALER - Kristian Wahyudi (Business and Entrepreneurial Review, 2016)
The purpose of this study was to influence the Service Recovery Justice Perceived Satisfaction and Impact on Relationship Quality, and Purchase Intention at PT Indotruck Utama As One Volvo Trucks Dealer Indonesia. The study design was a survey with causality analysis of quantitative methods. The population in this study is that consumers Volvo truck Indonesia. The sample selection using sampling nonprobability with 100 respondents. This study uses primary data derived from questionnaires. Mechanical questionnaires using Likert scale measurement. Data were analyzed using structural equation modeling (SEM) with the help of program LISREL 8.8. The results showed that procedural justice is proven positive effect on service recovery satisfaction, distributive justice is not a positive influence on service recovery satisfaction, interaction justice proven positive effect on service recovery satisfaction, service recovery satisfaction proven to have a positive influence on relationship quality, and service recovery satisfaction proved have a positive influence on purchase intention in PT. Top Indotruck as one of the Volvo Trucks dealer Indonesia. Complaint handling service recovery after a failure of the service used as one way to establish an ongoing relationship and be useful for the PT. Top Indotruck. The management should aim at customer satisfaction as much as possible so as to provide a sense of comfort and content for consumers, a grievance effective given the management of dealer Volvo Trucks Indonesia through service restoration can strengthen the quality of positive relationships that attract consumers to make purchasing decisions on product Volvo